UTILIZATION OF COCONUT SHELLS INTO CHARCOAL BRIQUETTES AS AN ALTERNATIVE FUEL: PEMANFAATAN TEMPURUNG KELAPA MENJADI BRIKET ARANG SEBAGAI BAHAN BAKAR ALTERNATIF - Yuliah Yuliah; Muhamad Andi Dzikri; Masri Masri; Exsa Darmawan; Atikah Yuliana (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Coconut is a plant that is found on the coastline, even in almost every region in Indonesia, coconut trees are also very axisr if cultivated, even in Indonesia itself coconut trees are often called versatile trees. Coconut has many benefits ranging from roots, trees, leaves to fruits. One of them is mekarwangi village, which is one of the abundant coconut producers. The large number of coconut trees in Mekarwangi Village causes a lot of coconut shells that are not used optimally so that they can become waste in the community. Coconut shells can be converted into briquettes that can be used as an environmentally friendly alternative fuel, while in middle eastern countries charcoal packages are used for roko purposes shisha pipes typical of the middle east. Therefore, it is necessary to increase understanding and awareness in the processing of coconut shells into briquettes through training to the community in order to increase the added value of waste so that it can become additional income for the people of Mekarwangi Village. This training was attended by 25 participants including village officials, housewives along with community leaders and also students and the Community Service team as implementers. The process of making coconut shell charcoal briquettes starts from cleaning coconut shells, burning, grinding, printing and drying